Anemia in Infants Born to HIV Infected Mothers in Uttaradit Hospital - Itsaradisaikul, Suluk (Health Science Clinical Research, 2022)
ABSTRACT Objective: Evaluate the prevalence of anemia in infants who are born to HIV-infected mothers. To identify factors associated with anemia in infants who are born to HIV-infected mothers. Methods: Retrospective cross-sectional analytical study, enrolled all infants who had HIV-infected mothers and were born in Uttaradit hospital, from 1st January 2015 to 31st December 2019. Demographic data (e.g., age, sex, body weight, gestational age, and maternal data during pregnancy) were recorded. Anemia at birth and 1-month old classify by hematocrit < 39% and < 28.5% respectively. Factors associated with anemia were analyzed. Results: 135 patients have met the inclusion criteria. The prevalence of anemia at birth and 1-month old were 5.19 % and 36.3% respectively. Maternal mean corpuscular volume (MCV) less than 80 fL was associated with anemia at birth. (Adj. OR 11.68, 95%CI 1.30-10.89) (p= 0.028) Post-exposure prophylaxis for HIV in high-risk infants who received Zidovudine (AZT), Lamivudine (3TC), and Nevirapine (NVP) was associated with anemia at 1-month old (Adj. OR 2.18, 95%CI: 1.01-4.69) (p=0.046) whereas the maternal diagnosis of HIV infection before pregnancy reduced risk of anemia in the infant at 1-month old. (Adj. OR 0.38, 95%CI: 0.18-0.82) (p=0.013) Conclusion: Prevalence of anemia at birth and 1-month old were 5.19% and 36.3% respectively. Infants who received AZT, 3TC, and NVP for post-exposure prophylaxis HIV infection were associated with anemia at 1-month old. Maternal diagnosis of HIV infection before pregnancy reduced the risk of anemia in infants at 1-month old. Keywords: anemia, infant, HIV, mother